Dosimetric characteristics of 3D-printed and epoxy-based materials for particle therapy phantoms - Brunner, Jacob; Langgartner, Lorenz; Danhel, Hannah; Birkfellner, Wolfgang; Richter, Christian; Wagenaar, Dirk; Stock, Markus; Georg, Dietmar; Knäusl, Barbara (Frontiers in Physics, 2024)
Objective: 3D-printing has seen use in many fields of imaging and radiation oncology, but applications in (anthropomorphic) phantoms, especially for particle therapy, are still lacking. The aim of this work was to characterise various available 3D-printing methods and epoxy-based materials with the specific goal of identifying suitable tissue surrogates for dosimetry applications in particle therapy. Methods: 3D-printed and epoxy-based mixtures of varying ratios combining epoxy-resin, bone meal and polyethylene powder were scanned in a single-energy CT, dual-energy CT and µCT scanner. Their CT-predicted attenuation was compared to measurements in a 148.2 MeV proton and 284.7 MeV/u carbon ion beam. The sample homogeneity was evaluated in the respective CT images and in the carbon beam additionally via widening of the Bragg peak. To assess long-term stability attenuation, size and weight measurements were repeated after 6 to 12 months. Results: Four 3D-printed materials acrylonitrile butadiene styrene, polylactic acid, fused deposition modelling printed nylon & selective laser sintering printed nylon and various ratios of epoxy-based mixtures were found to be suitable tissue surrogates. The materials' predicted stopping power ratio matched the measured stopping power ratio within 3 % for all investigated CT machines and protocols, except for µCT scans employing cone beam CT technology. The heterogeneity of the suitable surrogate samples was adequate with a maximum Bragg peak width increase of (11.5 ± 2.5) %. The repeat measurements showed no signs of degradation after 6 to 12 months. Conclusion: Of the investigated materials we identified surrogates for soft tissue and low to medium density bone. This allows low-cost, adaptable phantoms to be built for quality assurance and end-to-end tests for particle therapy.